2018
DOI: 10.1089/ten.teb.2018.0073
|View full text |Cite
|
Sign up to set email alerts
|

Pulp Regeneration Concepts for Nonvital Teeth: From Tissue Engineering to Clinical Approaches

Abstract: Following the basis of tissue engineering (Cells-Scaffold-Bioactive molecules), regenerative endodontic has emerged as a new concept of dental treatment. Clinical procedures have been proposed by endodontic practitioners willing to promote regenerative therapy. Preserving pulp vitality was a first approach. Later procedures aimed to regenerate a vascularized pulp in necrotic root canals. However, there is still no protocol allowing an effective regeneration of necrotic pulp tissue either in immature or mature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 198 publications
0
34
0
Order By: Relevance
“…Different authors [32,33] have found that that the cell homing approach, which does not involve the ex vivo culture of autologous cells is the best, most useful and cost-effective strategy for pulp regeneration in dental tissue engineering. Pulp regeneration has become a reality and has been facilitated through molecular and developmental biology or experimental embryology, as well as the biomimetic principles, which mimics the biological processes [34][35][36][37].…”
Section: Bioengineering Techniques or Approaches That Facilitate Dentmentioning
confidence: 99%
“…Different authors [32,33] have found that that the cell homing approach, which does not involve the ex vivo culture of autologous cells is the best, most useful and cost-effective strategy for pulp regeneration in dental tissue engineering. Pulp regeneration has become a reality and has been facilitated through molecular and developmental biology or experimental embryology, as well as the biomimetic principles, which mimics the biological processes [34][35][36][37].…”
Section: Bioengineering Techniques or Approaches That Facilitate Dentmentioning
confidence: 99%
“…2 Currently, tissue engineering technology has been regarded as a promising strategy of regenerative endodontics. 3…”
Section: Introductionmentioning
confidence: 99%
“…The presence of TGF-β expression in the dental pulp tissue suggests its potential role in the regulation of dental pulp cell functions during physiological and pathological processes [9,10]. Being a large family of signaling proteins, TGF-β is involved in several cellular events, including immune response, chemotaxis, odontoblast differentiation, DPSC proliferation and differentiation, as well as production and secretion of dentin matrix [10,11]. Three different isoforms of TGF-β have been identified in mammals, TGF-β1, TGF-β2, and TGF-β3, with similar biological activities.…”
Section: Resultsmentioning
confidence: 99%